2019
DOI: 10.1186/s12864-019-5741-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of stable QTLs and candidate genes involved in anaerobic germination tolerance in rice via high-density genetic mapping and RNA-Seq

Abstract: Background Anaerobic germination tolerance is an important trait for direct-seeded rice varieties. Understanding the genetic basis of anaerobic germination is a key for breeding direct-seeded rice varieties. Results In this study, a recombinant inbred line (RIL) population derived from a cross between YZX and 02428 exhibited obvious coleoptile phenotypic differences. Mapping analysis using a high-density bin map indicated that a total of 25 loci were detected across two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 49 publications
3
41
0
Order By: Relevance
“…Present findings revealed 38 putative QTLs for 6 traits on chromosomes 1,2,3,4,5,6,7 and 10. Several studies have been reported that usually QTL cluster responsible for correlated traits lie in the same genomic region confirming stable QTL (Gimhani et al 2016;Marathi et al 2012;Yang et al 2019). This QTLs cluster of different traits may be due to the presence of pleiotropy or Sabouri and Sabouri (2008), Zang et al (2008) tight linkage of genes controlling the traits (Gao et al 2013;Gimhani et al 2016).…”
Section: Discussionmentioning
confidence: 72%
“…Present findings revealed 38 putative QTLs for 6 traits on chromosomes 1,2,3,4,5,6,7 and 10. Several studies have been reported that usually QTL cluster responsible for correlated traits lie in the same genomic region confirming stable QTL (Gimhani et al 2016;Marathi et al 2012;Yang et al 2019). This QTLs cluster of different traits may be due to the presence of pleiotropy or Sabouri and Sabouri (2008), Zang et al (2008) tight linkage of genes controlling the traits (Gao et al 2013;Gimhani et al 2016).…”
Section: Discussionmentioning
confidence: 72%
“…Lack of tolerance to anaerobic germination (AG) results in insufficient energy supply for the growing embryo under oxygen deficit conditions caused by submergence [6]. Some rice genotypes have been reported to germinate under submerged conditions, however, only the tolerant genotypes survive by extending their coleoptiles or shoots above water, under declined oxygen levels [7].…”
Section: Introductionmentioning
confidence: 99%
“…Together, the TFGS QTLs explained 11.2% of PV. Three major QTLs on chromosomes 11 and 12 that (Han et al 2007), and qCD-9-3 and qCV-9 (Yang et al 2019) controlled the ESG-related trait VI-1 were qVI-1 11.2 , qVI-1 12.1 , and qVI-1 12.2 , with PV of 13.4%, 10.8%, and 10.2% and a LOD score of 5.21, 4.16, and 3.9, respectively (Table 5 and Fig. 3).…”
Section: Snp Markers For Qtl Mappingmentioning
confidence: 99%